EFFECT OF RAPID WEIGHT LOSS ON DECISION-MAKING PERFORMANCE IN JUDO ATHLETES - Leonardo de Sousa Fortes; Hugo Augusto Alvares da Silva Lira; Maria Elisa Caputo Ferreira (Journal of Physical Education)
ABSTRACT To date no studies investigated the effect of an intervention on the decision-making in combat sports athletes. The aim of this study was to analyze the effect of rapid weight loss methods on the performance of decision-making in judokas. Thirty-nine male judo athletes were selected on a non-probabilistic way and randomly divided in experimental (EG) and control (CG) groups. Forty-eight hours before the beginning of data collection, athletes were submitted to anthropometrical measurements and performed a simulated fight of judo, which was filmed. The weight lossin the EG was conducted to generate a mean loss of 5% per week during 2 weeks. There was a group and moment interaction (p<0.01) for body mass, with decrease only for the EG (p=0.01). There was also a group and moment for the GPAI index (p<0.01), with an improvement only in the CG (p=0.01). It was concluded that the rapid weight loss methods were not a good strategy for performance optimization in decision-making judokas.